The Statistical Analysis of Multidimensional Psychological Characteristics and User Feedback Willingness - Haiying Wang; Yaning Li; Chang Zhou; Haizhe Jin; Lin Wang (Advances in Mathematical Physics)
The purpose of this paper is to study the influence of multidimensional psychological characteristics on users’ feedback intention by using several statistical analysis methods based on information theory. The feedback process can be described as a communication process based on information theory. The feedback information entropy is associated with the degree of uncertainty elimination of the users who provide feedback information. Many factors are related to this uncertainty, such as information senders often stopped feedback process for some reasons and information senders may have provided fake or spam information. In order to encourage more useful feedback information, a model of a user’s willingness to provide feedback was established with personality traits and cognitive styles as independent variables, feedback motivation as intermediary variables, and feedback willingness as the dependent variable. 206 online and offline questionnaires were obtained to be analyzed by correlation analysis, regression analysis, and structural equation analysis. Cronbach’s α coefficient was used to test the reliability of the questionnaire, and exploratory factor analysis method was used to verify the validity of the questionnaire. First, correlation analysis was used to explore the correlation between personality traits, cognitive styles, and motivation factors. Second, we further explored the strength of the relationship of the five correlated groups of variables through linear regression analysis. At last, we conducted structure equation analyses to test the hypotheses. The results show that both personality traits and cognitive styles can have a significant impact on feedback motivation factors and also show that self-efficacy may be the only evident feedback motivation to encourage useful feedback information. The results show that the willing users with extraversion trait are more likely be motivated by self-efficacy and thus have evident feedback willingness.